Perfil das fraturas supracondilianas do úmero em crianças e avaliação da correção da fratura - Guterres, Leonardo Waihrich (2023)
Supracondylian humerus fractures occur in the distal region of the humerus and may account for 55% to 80% of all children elbow fractures. The majority occurs in male patients and the most associated trauma mechanism is hyperextension. Nowadays the treatment of these fractures is still guided by the Gartland classification, which was described in 1959. Among the treatments that can be used are non-surgical, closed reduction and fixation with Kirschner wires (and there are several techniques described for this fixation) and surgical reduction where the posterior and anterior approach are the most used. It is uncommon to observe neurological or arterial injury associated with these fractures, but limitation of movement with loss of function and varus or valgus deformities may be observed more frequently. The radiological evaluation of the carrying angle or valgus angle or Baumann carrying angle, as well as the evaluation of the Lateral capitellohumeral angle are possible ways to evaluate the complications. Likewise, the presence of functional loss. The evaluation of patients using the Innoccenti criteria, a combination of measuring the Baumann carrying angle, the measuring of loss of function and finding the presence of pain and/or neurological injury, is an important way of functional clinical assessment of patients and also a method to classifying the final treatment in four possible conditions: excellent, good, regular and poor. This study aims to describe the population profile of pediatric patients (those aged up to 14 years and 6 months) diagnosed with supracondylian humerus fracture treated at the Orthopedics and Traumatology Service of the University Hospital of Santa Maria. A cross-sectional study was carried out from September 2016 to December 2020. The convenience sample consisted of 127 patients. The mean age of the studied population was 6.22 years with a standard deviation of 2.87. Male gender was more prevalent and older than female gender (p=0.019) and the groups were homogeneous (p=0.459). Gartland III fractures corresponded to 58.3% (74) of the cases, followed by Gartland II 37% (47) and Gartland I 4.7% (6). Nerve and arterial injuries were observed in 6.3% (8) of the cases. The treatment performed through closed reduction and Kirschner wire fixation was performed in 74% (94) of the cases and in 21.3% (27) surgery was the treatment of choice. The median observed for the Baumann carrying angle was 74.1º and for the lateral capitellohumeral angle, 31º. Considering Innoccenti's criteria, 82.68% of the treated patients were classified as good results.